1997
DOI: 10.1128/cdli.4.2.113-116.1997
|View full text |Cite
|
Sign up to set email alerts
|

The level of lipopolysaccharide-binding protein is significantly increased in plasma in patients with the systemic inflammatory response syndrome

Abstract: Currently, there is no way to predict with a high degree of sensitivity and specificity which patients are likely to develop systemic inflammatory response syndrome (SIRS) following systemic infection, trauma, organ rejection, or blood loss. The level of human lipopolysaccharide-binding protein (LBP) was determined in the plasma of 22 patients with a clinical diagnosis of early SIRS. Twenty-nine plasma samples from healthy volunteers were used as controls. The mean level of LBP in the plasma of healthy volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 28 publications
3
37
0
5
Order By: Relevance
“…Differences in the two patient populations could also affect the observed differences in LBP levels. It should be noted that the LBP values for RA subjects reported by Wen et al (90) were comparable with those reported for sepsis and other severe illnesses (73,94,95). Furthermore, their reported CRP values were substantially higher than those for our cohort.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Differences in the two patient populations could also affect the observed differences in LBP levels. It should be noted that the LBP values for RA subjects reported by Wen et al (90) were comparable with those reported for sepsis and other severe illnesses (73,94,95). Furthermore, their reported CRP values were substantially higher than those for our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…Lysozyme is an important bacteriolytic enzyme produced by monocytes, macrophages, neutrophils, dendritic cells and glandular cells (52,97). The antimicrobial potential of lysozyme is derived from its ability to hydrolyze the glycosidic bond of peptidoglycan, which is found in the cell walls of both Gram-positive and Gram-negative bacteria (94). In circulation, lysozyme facilitates the degradation of bacterial peptidoglycan into peptidoglycan monomers.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous investigators, LBP is both a bacterial translocation biomarker and an acute phase protein identifying the presence of systemic infection. 20 Studies in humans have shown that LBP concentration increased in the presence of bacterial infection. [20][21][22] In our cohort, LBP was highly correlated with other markers of infection Previous investigators have demonstrated that LBP levels were increasing with severity of cirrhosis and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…20 Studies in humans have shown that LBP concentration increased in the presence of bacterial infection. [20][21][22] In our cohort, LBP was highly correlated with other markers of infection Previous investigators have demonstrated that LBP levels were increasing with severity of cirrhosis and portal hypertension. 23,24 High levels were also determined in cirrhotics with ascites compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with sepsis, LBP levels are high. 7 Consequently, LPS is efficiently solubilized, resulting in high numbers of LPS-LBP complexes and the inflammatory response continues to grow as more of these complexes are presented to responsive immune cells. LPS signal transduction pathways.…”
Section: Lps-mediated Activation Of Peripheral Blood Monocytesmentioning
confidence: 99%